2021
DOI: 10.1038/s41598-021-86971-z
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced dispersibility of flushable wet wipes after wet storage

Abstract: Scientific publications and newsfeeds recently focused on flushable wet wipes and their role in sewage system blockages. It is stated that although products are marked as flushable, they do not disintegrate after being disposed of via the toilet. In this work it is shown that wetlaid hydroentangled wet wipes lose their initially good dispersive properties during their storage in wet condition. As a consequence, we are suggesting to add tests after defined times of wet storage when assessing the flushability of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Recent studies on wet wipe dispersibility (Harter et al. 2021), and the presence of nonflushable and flushable wipes in marine sediments highlight the importance of additional research needed on this issue (Briain et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on wet wipe dispersibility (Harter et al. 2021), and the presence of nonflushable and flushable wipes in marine sediments highlight the importance of additional research needed on this issue (Briain et al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the sewerage systems of big cities like New York and London, the rise in wet wipes being used as toilet tissue and flushed into the sewer system by residents has led to a phenomenon known as "fatbergs," whereby this waste combines with other garbage and fats to create large masses clogging up sewer systems (Alda-Vidal and others, 2020). Although marketed as "flushable wet wipes," they do not disintegrate well after disposal, and in the U.S. up to $1 billion a year is spent dealing with the problem (Harter and others, 2021;Bowden, 2019). Awareness campaigns like "Trash It.…”
Section: Consume Sustainablymentioning
confidence: 99%
“…Dispersibility ageing has been introduced in a recent publication, 23 where it was demonstrated that pilot-scale produced hydroentangled, wetlaid wet wipes can deteriorate their dispersibility over time, when stored in wet condition. The MMCF/synthetic fibres in a wet wipe were found to have no impact on this effect, which is supported by the results in Figure 5.…”
Section: Dispersibility Ageingmentioning
confidence: 99%
“…Wet wipes were made from the produced nonwovens using deionized water to simulate the usually applied lotion. In a recent work, it was demonstrated that dispersibility ageing is similar in wipes treated with water and usual lotion, 23 which was applied to the 125 × 175 mm cut sheets in a gravimetric ratio of 1:3. The wet wipes were stored in sets of three in sealed plastic bags.…”
Section: Wet Wipe Productionmentioning
confidence: 99%
See 1 more Smart Citation